Carbon content in the above-ground biomass of evergreen forest in Chile - Gayoso A., Jorge; Guerra C., Javier (Bosque (Valdivia), 2005)
Carbon (C) content in stem, branches, leaves and bark from 16 tree species of the native forest in Chile was determined. The mean contents of organic C by species varied between 34.9% and 48.3% and the single mean was 43,7í0.16%. The total C content was 5,5í0.76% higher than the organic C content. Significant differences between groups of species and tree tissues were found. For all the species the stem’s C contents (44,4í0.16%) were slightly higher than those in woody branches, leaves and bark (43,5í0.21%). The highest C content was for Saxegothaea conspicua with 47,8í0.38% and the lowest for Weinmannia trichosperma, 42,6í0.54%. Through analysis of variance, the study didn’t show significant differences between deciduous species and evergreen species and forest type as it did for native coniferous and broadleaf.